Urgensi Bahasa Arab Bagi Da’i - Intan, Hilda Marni (Alhurriyah, 2012)
This paper attempts to reflect the urgency of Arabic language support for the preachers in delivering mission kindness "amar mruf nahi munkar". Arabic is the language of the sources of Islamic law, the Quran and Sunnah. It is a false preachers do not need to understand Arabic. Therefore, this paper aims to mistaken views can be minimized without having to revise the law verses and verses of a general nature and universal.